Evaluation of User Interface and User Experience on Solo Destination App using System Usability Scale and Human-centered Design Methods - Muhammad Wildan Yasykur; Devi Ajeng Efrilianda (Journal of Advances in Information Systems and Technology, 2024)
User interface (UI) and user experience (UX) play a crucial role in determining a system's usability. Although designed for widespread use, the Solo Destination app has not been assessed for its usability. This study evaluates the app using the System Usability Scale (SUS) and Human-Centered Design (HCD) methods. The sample size was determined using Slovin’s formula, resulting in 50 participants, with 5 chosen for in-depth interviews to gain deeper insights. The initial evaluation showed that the app scored 55.55 on the SUS, placing it in the marginal low category within the acceptability range. This score corresponds to a grade scale of D and an "OK" adjective rating. Interviews conducted during the inspiration phase provided detailed data for the subsequent ideation phase, where brainstorming identified seven main issues: features, reminders, event updates, information delivery, color, layout, and hierarchy. In the implementation phase, solutions to these issues were developed into a prototype using Figma. The improved prototype was then retested using the same methods. The retest showed a significant improvement, with the SUS score rising to 82.05. This places the app in the acceptable category, with a grade scale of B and a "good" adjective rating. This research highlights the importance of continuous usability evaluation and user focused design. Addressing identified issues significantly enhanced the app’s usability, ensuring better user acceptance and satisfaction.